Physical characterization of a suite of Buzzard Coulee H4 chondrite fragments. (3rd June 2013) - Fry, C.; Melanson, D.; Samson, C.; McCausland, P. J. A.; Herd, R. K.; Ernst, R. E.; Umoh, J.; Holdsworth, D. W.
Abstract: On November 20, 2008, the Buzzard Coulee H4 chondrite fell to Earth outside of Lloydminster, Alberta, Canada. Eighteen fresh samples obtained by the National Meteorite Collection of Canada, ranging from 8.80 to 109.14 g, were investigated in this study. Physical properties of the samples were first obtained using a suite of nondestructive techniques. The bulk density (Archimedean bead method: 3.48 ± 0.04 g cm −3 ; 3‐D laser imaging: 3.46 ± 0.03 g cm −3 ; micro‐computed tomography: 3.44 ± 0.03 g cm −3 ), porosity (6.2 ± 0.1%), bulk magnetic susceptibility (log χ: 5.364 ± 0.056 × 10 −9 m 3 kg −1 at 825 Hz; 5.329 ± 0.052 × 10 −9 m 3 kg −1 at 19, 000 Hz), and other derived magnetic properties (frequency dependence: 8.7 ± 6.2%; degree of anisotropy A %: 22.0 ± 2.0%; ellipsoid shape B %: −18.7 ± 8.7%) are typical of H chondrites. The coefficient of variation associated with the properties measured directly was low (0.10–1.15%), indicating that the samples are homogenous at the interfragment scale. The study then proceeded with detailed analyses at the intrafragment scale. Visual inspection of micro‐computed tomographic images allowed the identification of an anomalous large clast with low metal content in a fragment. Another fragment exhibited macroscopic shock veins that warranted further examination. These fragments were cut and polished thin sections prepared for petrological analysis by optical and scanning electron microscopy. Based on mineralogical and textural similarities with several chondrules, the large clast was interpreted to be a macrochondrule. In a larger context, this study proposes a protocol for the systematic investigation of extraterrestrial material that can be exported to other new meteorite falls and finds, and specimens from sample return mission.